Impementasi Simple Additive Weighting Sebagai Model Pengambilan Keputusan Menentukan Kelayakan Beasiswa Di STIT Pringsewu - Sri Hartati; Wiku Viktor Yadi; Muhammad Masrur; Muhammad Idris (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2022)
Scholarship acceptance for high school education level must hit the right targets, so as not to get the wrong target. Therefore, there is a need for a decision-making system model design to determine the feasibility of receiving scholarships in high schools, the right method for determining the eligibility of scholarship recipients is the Simple additive weighting method. This method was chosen because it is able to select the best alternative from a number of alternatives. The simple additive weighting method is often also known as the weighted addition method. The basic concept of the Simple additive weighting method is to find the weighted sum of the performance ratings for each alternative on all attributes. In this case, the alternative referred to is those who are entitled to receive scholarships based on the criteria of academic achievement index (GPA), behavior on campus, parental income, number of dependents of parents, number of siblings, organizational activities, and the number of verses and memorizing Al-Quran. . After determining the criteria, the system is tested using manual calculations involving six alternatives as the sample being tested. From the alternatives tested, the highest score was 0.96 which became the priority for prospective recipients of scholarship assistance for STIT Pringsewu students.